Influencia : obtener compromiso para lograr resultados - Scharlatt, Harold; Smith, Roland (Ideas into action guidebooks., 2015)
Influence is an essential component of leadership. Your position in an organization and the power it gives you aren't always enough to motivate people to do what you ask. You may negotiate with or persuade people to make short-term behavioral change, but to create sustained change, you will need to influence them, which includes negotiation, persuasion, and other methods. Developing your skill at using different influence tactics can help you achieve results when you use those tactics to get support from direct reports, peers, bosses, and even clients and vendors.